Prognostic significance of severe mitral annular calcification in aortic stenosis: implications for aortic valve replacement outcome - Valeria Pergola; Dan-Alexandru Cozac; Maria Teresa Savo; Saima Mushtaq; Raffaella Motta; Roberto Pedrinelli; Pasquale Perrone-Filardi; Gianfranco Sinagra; Morena De Amicis; Maria Vittoria Chiaruttini; Gabriele Cordoni; Giulia Lorenzoni; et al. (International Journal of Cardiology: Heart & Vasculature)
Background: Mitral annulus calcification (MAC) is no longer seen as merely age-related. Recent evidence links MAC to calcific aortic stenosis (AS), but its prognostic value in AS patients undergoing aortic valve replacement (AVR) remains unclear. This study aims to assess the impact of cardiac CT-derived MAC on cardiovascular outcomes in this population. Methods: Pre-procedural contrast-enhanced CCT was performed, and Guerrero CCT-derived MAC score was used to quantify the MAC severity. Major adverse cardiovascular events (MACE − cardiovascular mortality, significant arrhythmias [sustained ventricular tachycardia, asystole, complete atrioventricular block], stroke, hospitalizations due to heart failure) and all-cause and non-cardiovascular mortality were assessed during the 60 months of follow-up after AVR. Multivariate Cox models evaluated the predictive value of severe MAC alongside other significant variables. Results: A total of 313 patients with severe AS and subsequent AVR were included in the study. Among these, 34.6 % of patients had no criteria for MAC, while 65.4 % exhibited MAC (54.1 % presented mild MAC, 33.6 % moderate MAC, and 12.1 % severe MAC). In multivariable Cox models, severe MAC, moderate-to-severe mitral regurgitation, and Society of Thoracic Surgeons (STS) score > 2.5 % remained independent predictors of MACE (all p < 0.05). Also, severe MAC and STS scores > 2.5 % remained independent predictors of all-cause mortality (all p < 0.05) in multivariable analysis. Conclusion: The present study demonstrated that severe MAC independently predicted worse outcomes in patients undergoing AVR, suggesting that incorporating it into the clinical evaluation could ensure a critical change in patient care.